Applied Knowledge and Augmented Reality – Bridging the gap between learning and application - Jana Gonnermann-Müller; Philip Wotschack; Martin Krzywdzinski; Norbert Gronau (Industry 4.0 Science, 2025)
The increasing complexity of industrial environments demands new competencies from workers, particularly the ability to interact with advanced digital systems. Traditional training methods often fall short in supporting the effective transfer of applied knowledge to such contexts, and the effectiveness of this transfer, as measured by performance-based outcomes, remains to be investigated. To address this gap, the present study employed a between-subjects experimental design comparing augmented reality- and paper-based instructions within a realistic production training scenario. The results show that participants who learned with augmented reality completed the production process significantly faster and with fewer errors than those using paper instructions. In addition, learners using augmented reality reported higher usability and experienced lower cognitive load during training. These findings suggest that augmented reality can enhance the transfer of practical skills in industrial settings, supporting more efficient and accurate task execution. Future research should validate these results with larger and more balanced samples.
Keywords: 330; Augmented Reality; digital transformation; knowledge transfer; learning and training; learning factories